Impact of Low Hemoglobin on Body Composition, Strength, and Redox Status of Older Hemodialysis Patients Following Resistance Training - da Silva, Victor; Corrêa, Hugo; Neves, Rodrigo; Deus, Lysleine; Reis, Andrea; Souza, Michel; dos Santos, Cláudio; de Castro, Danilo; Honorato, Fernando; Simões, Herbert; Moraes, Milton; Schoenfeld, Brad; et al. (Frontiers in Physiology, 2021)
Introduction The purpose of this study was to: (i) investigate the effect of six months of resistance training (RT) on body composition, muscle strength, hematological patterns, and redox profile in maintenance hemodialysis (HD) patients, and; (ii) evaluate the effects of baseline concentrations of hemoglobin on the RT response. Methods One hundred fifty-seven subjects with chronic kidney disease (CKD) were randomly allocated into two groups: Control [CTL, (n = 76)] and RT (n = 81). A first visit was required for anamnesis and anthropometric measurements. Venous blood samples were collected at baseline and after twenty-four weeks of training in all patients for the analysis of clinical and redox balance markers. The RT program spanned six months and consisted of three sets of 8–12 repetitions with a rating of perceived exertion between 5 and 8 for three weekly sessions. Each exercise session was performed in twelve resistance exercises and it least for approximately 40 min. Results The main results demonstrated that RT decreased waist circumference by 3%, and decreased thiobarbituric reactive species (TBARS) by 28%. Moreover, RT increased handgrip strength by 28.4%, fat-free mass by 4.1%, hemoglobin by 5%, iron by 33.4%, glutathione by 121%, and Trolox equivalent antioxidant capacity by 14.2% (p < 0.05). Low hemoglobin concentrations impaired the effect of RT on fat-free mass gain. Conclusion Six months of RT in HD patients improved clinical parameters, such as hemoglobin, iron, body composition, and redox balance, while low hemoglobin concentration impaired exercise-benefits on fat-free mass in patients with CKD. These findings can contribute to a better clinical application of RT in the maintenance of hemodialysis patients.